Diseño de una interfaz móvil sobre las actividades turísticas de la parroquia Eloy Alfaro cantón Latacunga - Chango Muso, Daysi Vanessa (2020)
The purpose of this research was to design an interface for mobile devices that would provide the inhabitants of the Eloy Alfaro parish with current and historical information about tourist activities that they can develop locally, giving value to what is around them. This Parish is a historical place in Latacunga city, where the necessity to revalue their heritage assets, which due to the scarcity of media and lack of knowledge of tourists lacks movement. The objective of the project was to design a mobile interface to publicize the tourist activities Eloy Alfaro parish, Latacunga canton. Its development included bibliographic research, where technical and theoretical knowledge was acquired about interface design and the relationship between graphic design and tourism; through documentary and field research, information was gathered about assets of heritage interest, as well as an inventory of their tourist attractions. The different stages of the user-centered design methodology made it possible to define a linear design that adapts the information in an interactive structure. The research techniques such as the survey, interview, observation and focus group, identified cultural manifestations that make known their customs and gastronomy, including places that their inhabitants intend to promote for tourism in order to generate economic income. The design of the prototype was based on the process of user-centered design, which proposes several stages that assume the entire process of design and development of the product, this being focused on the needs, characteristics and objectives of the user. As a result, from the information gathered, photographic research sheets were elaborated that allowed the use of graphic and multimedia media, which contributed to the design of an interface that informs the inhabitants of the Eloy Alfaro Parish about tourist activities as a means of easy access and usability, which allowed the generation of a different experience when visiting their Parish. Concluding that the established needs are solved through concrete ideas, reflected in design projects with innovation